Prenatal Diagnosis of a Retroesophageal Left Brachiocephalic Vein: Two Case Reports. (4th March 2017) - Cheng, Yvonne Kwun Yue; Law, Kwok Ming; Chak, Pui Kwan; To, Ka Fai; Chan, Yiu Man; Leung, Tak Yeung
Abstract : A retroesophageal left brachiocephalic vein is an extremely rare anomaly and has only been reported in 6 postnatal cases. Two prenatally diagnosed cases are reported. On the 3‐vessel view, the vein appears as an aberrant vessel transversely coursing behind the aorta and trachea, which subsequently drains into the superior vena cava, giving rise to a U‐shaped configuration. On color Doppler sonography, the U sign is bicolored. This anomaly should prompt the sonographer to carefully assess for other congenital heart defects, suggest consideration for genetic testing, and alert the cardiologist because it could affect central line procedures and cardiac interventions after delivery.